Markers of inflammation in patents with type 2 diabetes and cardiovascular form of diabetic autonomous neuropathy - Irina Arkad'evna Bondar'; Olesya Yur'evna Shabel'nikova (Сахарный диабет)
Aim. To determine the level of inflammation markers and their relation to endothelial dysfunction and insulin resistance in patents with type 2 diabetesmellitus and cardiovascular form of diabetic autonomous neuropathy. Materials and methods. A total of 87 patients aged 45-66 years were examined for blood insulin level, insulin resistance index (HOMA-IR), CRP,and anti-inflammatory cytokine (TNF-a, IL-1-beta, IL-6) levels. Endothelial dysfunction was estimated based on quantitative Willebrand factorassay. Vegetative disorders were detected from reflex cardiovascular ECG data. Results. The development of cardiovascular form of diabetic autonomous neuropathy in patents with type 2 diabetes depended on diabetes duration,quality of carbohydrate metabolism compensation, levels of hyperinsulinemia and insulin resistance. Mean levels of Willebrand factors andinflammation markers in patents with type 2 diabetes and overt vegetative dysfunction were significantly higher than in diabetic patients withoutautonomous neuropathy. Correlation analysis revealed significant correlation of CRP and IL-6 levels with results of standard ECG tests. Conclusion. Results of the study demonstrate chronic inflammation in patents with type 2 diabetes and cardiovascular form of diabetic autonomousneuropathy. Increased level of inflammation markers and its relation to severity of vegetative disorders and endothelial dysfunction confirm the roleof inflammation in pathogenesis of nervous co-morbidity in patents with type 2 diabetes.